The Role of Gut Microbiota in the Prevention or Development of Atherosclerosis – A Review - Początek, Jakub; Piotrowski, Michał; Serwicki, Piotr; Pośpiech, Szczepan; Prosowski, Jakub (Quality in Sport, 2025)
Aim of the study: This study aims to consolidate current knowledge on the role of gut microbiota in atherosclerosis, examining its mechanisms of action, the impact of dietary patterns on microbial composition, and emerging therapeutic interventions. Materials and methods: A systematic review of scientific literature was conducted through PubMed, Google Scholar, and other databases, focusing on diagnostic advancements, insights into the role of gut microbiota in atherosclerosis, and innovative therapeutic methods. Main results: The findings reveal that gut microbiota exerts a dual influence on atherosclerosis development through its metabolites, with SCFAs offering anti-inflammatory and cardioprotective effects, while TMAO promotes endothelial dysfunction and pro-thrombotic states. Diet emerges as a critical factor, with fiber-rich and Mediterranean-style diets enhancing SCFA production and reducing TMAO levels, whereas Western diets exacerbate dysbiosis and atherogenesis. Conclusions: The gut microbiota represents a dynamic and modifiable target for the prevention and management of atherosclerosis. Advancements in diagnostic tools, dietary interventions, and microbiota-based therapies provide new opportunities to address cardiovascular health challenges.